Performance Measurement of Economic (Commercial) Activities - Zsidó, Kinga Emese; Gróf, Pál (Acta Scientiarum Socialium, 2015)
Performance Measurement of Economic (Commercial) Activities. Information on business performance is essential in today’s competitive environment, and it could be one of the most valuable information for managers. Without it companies are unable to make deliberate and good decisions, to respond competitively to the changes in the market. A well implemented, thoughtful and systematic performance measurement activity can improve the company’s performance. Literature provides many useful and valuable methods to measure business performance. The most important question, however, is which one or which ones of those methods and procedures can provide the most valuable information. The answer to question of which measurement methods and procedures to select depend on the company’s specific activity (producer, service, commercial, agricultural, etc.), on the characteristics of the products and/or services provided by the company, on the company’s position, etc. This study helps to reveal the key factors in trading activity, to present the characteristics of trading activity and to select the most appropriate performance measurement indicators, methods and procedures, for this type of activity. The publication was supported by the SROP-4.2.2.B-15/1/KONV-2015-0001 project. The project has been supported by the European Union, co-financed by the European Social Fund.